Violencia familiar y su influencia en el comportamiento de un adolescente de 14 años de la ciudad de Babahoyo Provincia de Los Ríos - Aragundi Vera, Sani Jahaira (2022)
The present case study was carried out with the objective of verifying the influence of family violence on the behavior of a 14-year-old adolescent from the city of Babahoyo, province of Los Ríos. All this was carried out through the use of psychological techniques such as: Direct observation, clinical history, semi-structured interview and the application of psychological reagents "Beck Depression Inventory" and "Hamilton Anxiety Scale", in addition to the technique “Classification of CBT event, thought and emotion”. Which allowed the psychological evaluation carried out on the patient to be the ideal one to determine if said violence present in his home influences his behavior. In addition, it is necessary to mention that the qualitative methodology used in this work was directed directly to study variables such as: family violence and behavior of an adolescent, having said that, it is necessary to mention that the theoretical contribution and the practical contribution executed through the techniques of Cognitive Behavioral Therapy, allowed the initially stated objective to be satisfactorily fulfilled. On the other hand, it was possible to modify all those irrational beliefs that the patient manifested during the psychological intervention due to his current situation, which was achieved thanks to individual psychotherapy, which had as therapeutic goals to mitigate the emotional and behavioral problems referred by the patient. 14-year-old adolescent during all the sessions worked. Achieving in this way great results in improving their quality of life, allowing them to better reintegrate into their social, family and academic context.